SAT0541 Gout Patients Treated with Conventional Urate-Lowering Therapy: Association between Disease Control and Health-Related Quality of Life. (10th June 2014) - Wood, R.; Johnson, J.; Morlock, R.; Baumgartner, S.; Ramachandran, S.
Abstract : Background: Gout patients have impaired quality of life compared with the general population [1]. Gout is a chronic, progressive disease and many patients treated with conventional urate-lowering therapy (ULT) are inadequately controlled [2]. Implications of inadequate control can be assessed by studying the health-related quality of life (HRQoL) of patients receiving conventional ULT who are adequately controlled versus those who are not. Objectives: To evaluate the impact of inadequate control on HRQoL in gout patients. Methods: A retrospective database analysis of gout patients currently receiving conventional ULT for at least 3 months. Data were drawn from the Adelphi Disease Specific Programme (DSP)™, a cross-sectional survey of patients with gout in France, Germany, UK and US. Participating physicians submitted extensive clinical data for each patient including most recent serum uric acid (sUA) level and number of flares in last 12 mos. Patients were invited to complete a patient self-completion questionnaire, containing the EQ-5D (3L) and PROMIS HAQ. Inadequate control was defined as sUA level >6 mg/dL or ≥2 flares. Adequate control was defined as sUA level ≤6 mg/dL and 0 flares. Mann-Whitney tests investigated differences between inadequately controlled and adequately controlled patients in HRQoL. Results: Of 1204 gout patients in this analysis, 836 (69%) were inadequately controlled; 82% of patients were male, mean age was 61 yrs, and mean duration on current ULT was 32 mos. 368 (31%) patients were adequately controlled with a mean age of 63 yrs and mean duration on current ULT of 57 mos. There were no significant differences between patients deemed adequately controlled vs inadequately controlled on number of renal, autoimmune, GI or CV comorbidities. However, there was a significant difference in total EQ-5D scores between inadequately controlled and adequately controlled patients (-0.087; p<0.0001). Inadequately controlled patients had significantly worse PROMIS HAQ scores (-6.302; p<0.0001) compared with adequately controlled patients. Conclusions: Less than one-third of patients with gout were controlled. Patients with inadequately controlled gout reported significantly worse functioning and quality of life compared with adequately controlled patients, as measured by EQ-5D and PROMIS HAQ scales. New therapeutic approaches are needed to improve control in gout patients. References: Roddy E. Rheumatology (Oxford) 2007;46:1441-4. Perez-Ruiz F. Adv Ther 2012;29:935-46. Acknowledgements: Research sponsored by Ardea Biosciences/AstraZeneca. Disclosure of Interest: R. Wood Employee of: Adelphi Real World, J. Johnson Employee of: Adelphi Real World, R. Morlock Employee of: Ardea Biosciences, Inc, S. Baumgartner Employee of: Ardea Biosciences, Inc, S. Ramachandran Employee of: AstraZeneca DOI: 10.1136/annrheumdis-2014-eular.4429